1997
DOI: 10.1136/jnnp.63.5.579
|View full text |Cite
|
Sign up to set email alerts
|

Response of parkinsonian swallowing dysfunction to dopaminergic stimulation

Abstract: Objectives-To determine the degree of dopaminergic response of swallowing dysfunction in Parkinson's disease. Methods-Fifteen patients with idiopathicParkinson's disease and symptomatic dysphagia were studied. All had motor fluctuations in response to long term levodopa therapy. On two separate days, after overnight withdrawal of all antiparkinsonian medication, a modified barium swallow using cinefluoroscopy and diVerent food consistencies was performed before and after administration of oral levodopa and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
132
2
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 173 publications
(142 citation statements)
references
References 22 publications
4
132
2
3
Order By: Relevance
“…Some studies did not have an adequate method of randomization for referral to different intervention groups, e.g., Iwasaki et al [23] and Bushman et al [27] did not score pre-versus posttreatment blinded for the schedule of treatment [4,24,[26][27][28], nor did they have an adequate placebo or control population [7,15,17,22,[26][27][28][29]. Very often a control group receiving no therapy for dysphagia when in fact an indication for treatment is present is regarded as unethical and therefore usually not approved by any medical ethical committee.…”
Section: Methodologic Problemsmentioning
confidence: 99%
See 2 more Smart Citations
“…Some studies did not have an adequate method of randomization for referral to different intervention groups, e.g., Iwasaki et al [23] and Bushman et al [27] did not score pre-versus posttreatment blinded for the schedule of treatment [4,24,[26][27][28], nor did they have an adequate placebo or control population [7,15,17,22,[26][27][28][29]. Very often a control group receiving no therapy for dysphagia when in fact an indication for treatment is present is regarded as unethical and therefore usually not approved by any medical ethical committee.…”
Section: Methodologic Problemsmentioning
confidence: 99%
“…Now it seems as if L-dopa failed to have an effect in an already normal radiologic pattern of deglutition, whereas the information of the total swallowing act was incomplete. In some articles no information was given about the Parkinson's disease severity scale [19,21,22,31]. Some authors did not describe the ''on'' or ''off''-motor phase during the examinations and therapy [7, 19-21, 23, 29, 31].…”
Section: Methodologic Problemsmentioning
confidence: 99%
See 1 more Smart Citation
“…27,28 In the present cohort, 6 of 26 patients were in the SIon group, suggesting that the effect may be more common than suspected. One possible explanation is that on-phase dysphagia is similar to a dyskinetic effect of medication on the swallowing pathway.…”
Section: Swallowing Impairments In Parkinson's Diseasementioning
confidence: 61%
“…Finally, it is worth noting that although there was no improvement in aspiration scores, levodopa treatment did reduce the number of secondary clearing swallows, in keeping with previous observations. 27 It has been suggested that rigidity and bradykinesia of oral musculature may compromise the oral preparatory phase, which is under volitional motor control. These are the symptoms most likely to be ameliorated by treatment, and it therefore would seem logical to have some improvement of oral bolus control.…”
Section: Swallowing Impairments In Parkinson's Diseasementioning
confidence: 99%